Angiotensin-Converting Enzyme (ACE) Insertion/Deletion (I/D) Polymorphism as a Conjoint Regulator of Coagulation, Fibrinolytic, and RAAS Pathway in Infertility and Associated Pregnancy Complications - Thakur, Sunil; Sharma, Vaishnavi; Kaur, Dipneet; Purkait, Pulakes (Journal of the Renin-Angiotensin-Aldosterone System, 2022)
Despite the increase in assisted reproductive technologies, the high rates of infertility and pregnancy complications are a major concern to infertility specialists worldwide. Infertility may be attributed to pregnancy complications like thrombophilia, preeclampsia and fibrin-induced recurrent pregnancy loss (RPL). Renin-angiotensin-aldosterone system (RAAS) directly or indirectly causes preeclampsia and thrombophilia through the fibrinolytic pathway that ultimately leads to RPL or infertility. The underlying mechanisms of this interaction are still unclear. The present comprehensive review is intended to demonstrate the role and interaction of RAAS and fibrinolytic pathways in pregnancy complications. How this interaction can induce pregnancy complications, and ultimately infertility, is also discussed in the light of current evidence. This study also presents common markers that link RAAS and fibrinolytic processes in developing thrombophilia, preeclampsia and RPL. The common link in these pathways is ACE gene I/D polymorphism. Apart from ACE, PAI-1, VIIa, XIIa, AT1R, AT1AA, and TF are common molecules that can delineate the underlying causes of pregnancy complications and infertility.